ANALISIS MARGIN PEMASARAN CENGKEH DI KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Bengkari, Moh. Junus; Manu, Rolens E.H. Riwu; Nggandung, Yeheskiel (Journal Economic Education, Business and Accounting, 2024)
The aim of this ressearch is to determinetion the size of marketing margin for cloves from farmers to users in Alor Regency, especially in North West Alor. This research aims to identify the most effective routes and determine optimal marketing margins in the region. The main focus of this research is to ensure large marketing margins for clove products in North West Alor Regency, with the aim of providing clove farmers with access to effective and profitable marketing routes. This ressearch use a qualitative method with a case study approacth. Data collection techniques involve observation and in-depth interview. Result of the research conducted show that there are many marketing channels in the region, causing the price difference from farmers to final consumers to remain very high. Keywords: marketing margin, revenue